The Relationship between Parenting Style and Career Planning of Vocational Students by Educational Psychology under Information Technology - Qian Zhang (Occupational Therapy International, 2022)
It is aimed at studying the role of parenting style on the career planning of vocational students in the context of information technology. This design takes the first-year and second-year students of two higher vocational colleges as the survey objects. From the perspective of educational psychology, firstly, the parenting style scale of these students is constructed, and meanwhile, the dimension design of career planning is carried out. Secondly, through the questionnaire survey, the career planning of students and the status quo of parenting styles are investigated, and the sample data are statistically analyzed by data analysis methods such as standard deviation analysis, cluster analysis, and correlation analysis. Finally, hypotheses are formulated and justified. The results reveal that the total score for career planning and the average score of each dimension are more than 3 points, indicating that vocational students have certain plans for their future careers. There are great differences in the gender of parenting styles, and the parental acceptance/involvement (t=3.389, p<0.01) dimension of the parenting style of the first-year students is greatly higher than that of the second-year students. On the dimension of psychological autonomy (t=−2.066, p<0.05), the score of second-year students is distinctly higher than that of the first year. There are obvious differences in grades from the dimensions of parental acceptance/participation and psychological autonomy. There is no observable difference in whether it is an only child (p>0.05) and the place of origin (p>0.05). In terms of the total score and each dimension of career planning, the authoritative type scored the highest, and the neglect type scored the lowest. Parents’ participation and acceptance behavior of vocational students are markedly related to their career planning. Parental punishment and acceptance are distinctly positively correlated with the career planning of these students and their two dimensions. Psychological autonomy is memorably associated with the domain of exploration.